Fabrication, Characterization, and In Vivo Evaluation of Famotidine Loaded Solid Lipid Nanoparticles for Boosting Oral Bioavailability. (14th December 2017) - Shafique, Muhammad; Khan, Mir Azam; Khan, Waheed S.; Maqsood-ur-Rehman,; Ahmad, Waqar; Khan, Shahzeb
Abstract : Famotidine as H2 receptor has antagonistic effects on gastric secretion. Unfortunately, its hydrophobic nature contributes to its variable and poor oral bioavailability. In the current study efforts are being made to fabricate famotidine loaded solid lipid nanoparticles with narrow size distribution. Prepared nanoformulations were pharmaceutically evaluated to confirm the desired boosted oral bioavailability. Famotidine loaded nanoformulation (FFSe-4) showed particle size 111.9 ± 1.3  nm, polydispersity index 0.464 ± 0.03, zeta potential −33.46 ± 2  mV, entrapment efficiency 84 ± 2.7 %, and drug loading capacity 2.709 ± 0.13 %. Drug-excipients compatibility was confirmed by Fourier transformed infrared spectroscopy. Scanning electron microscopy confirmed spherical shaped, nanosized particles. Differential scanning calorimetry and powder X-ray diffractometry confirmed the change in crystalline nature. Prepared nanoformulation was more stable at refrigerated temperature. In vitro study showed that drug release time is proportional to drug pay load and followed zero order kinetics. Release exponent (n > 0.5 ) confirmed non-Fickian-diffusion mechanism for drug release. In vivo pharmacokinetic studies showed 2.06-fold increase in oral bioavailability of famotidine dispersed in solid lipid nanoparticles compared to commercial product. These results authenticate solid lipid nanoparticles as drug delivery system and propose prolonged release with improved oral bioavailability for famotidine.